Treatment Adherence among HIV and TB Patients Using Single and Double Way Mobile Phone Text Messages: A Randomized Controlled Trial - Odette Dzemo Kibu; Vincent Verla Siysi; Same Ekobo Albert Legrand; Elvis Asangbeng Tanue; Dickson Shey Nsagha (Journal of Tropical Medicine)
Background. Research has shown that patients fail to adhere to ART and TB treatment due to the long duration of both therapies, side effects, and forgetfulness. Objective. To assess the role of the double-way and single-way SMS on adherence to HIV and TB treatment. Materials and Methods. A randomized controlled trial among adult HIV and TB patients on treatment at the Buea Regional and Kumba District Hospitals, South West Region, Cameroon, was conducted. Participants were randomly allocated to the control, single-way, and double-way SMS intervention groups. HIV and TB participants were followed independently for a period of 6 months and 3 months, respectively. Baseline and post-intervention data were collected and analyzed using the chi-square and Student’s t-tests with statistical significance set at p<0.05. Results. A total of 210 HIV participants and 84 TB were recruited into the study with a mean age of 41.25 ± 10 years and 37.89 ± 13.27 years, respectively. Optimal adherence to ART and TB treatment at baseline was [65 (31%) CI: 0.247–0.372] and [35 (41.7%) CI: 0.311-0.522], respectively, and after the intervention, it increased to [72 (42.6%) CI: 0.347-0.495] and 41 (61.2%), respectively. There was an increase in adherence to ART among participants in the double-way SMS intervention group from 23 (32.9%) (RR: 1.04, CI: 0.8-1.31, p=0.716) to 29 (48.3%) (RR: 1.06, CI: 0.75-1.50, p=0.746). Combined single-way and double-way SMS significantly increased adherence to ART. Conclusions. The level of adherence was low among HIV and TB participants. The single-way and double-way SMS did not significantly increase adherence. However, a combination of both the double-way and single-way SMS intervention significantly improved adherence to ART.